Performance Estimation of Solar Imagery Using Different Types of Atmospheric Turbulence Models - Ali, Huda S. (Iraqi Journal of Science, 2023)
This paper proposed several approaches for estimating the optical turbulence of the Earth’s atmosphere and their effect on solar images’ resolution using ground-based telescopes based on von Kárman, Kolmogorov, and modified von Kárman PSDs models. The results showed a strong correlation coefficient for the modified von Kármán model of atmospheric representation. As can be seen in the case where solar adaptive optics have been properly designed, they typically decrease aberration considerably and provide greatly improved imagery.